THE APPLICATION METHODS OF MEDIA TECHNOLOGIES IN PRACTICAL TRAININGS OF NATURAL GEOGRAPHICAL SCIENCES - F.A., Xamroyeva; L.Z., Ibragimov (International Journal of Psychosocial Rehabilitation, 2020)
The importance of practical training in geographical education, the purpose of training and its methodic requirements are demonstrated in this article. The detailed information is given about how to work with various maps and globes, digital indicators in the basics of practical training in geography education, forming of skills and qualifications such as, monitoring of natural phenomena, as well as the methodology of conducting practical training of natural geographic sciences is widely illuminated through media tools, information and communication technologies and software products.